Preparation and Characterization of Nitrile Butadiene Rubber (NBR)/Polyoxymethlene (POM) Blends Compatibilized by Maleic Anhydride Grafted POM (MAH-g-POM) - Luo, Jia-Qi; Yang, Bin; Cheng, Guo-Jun; Xia, Ru; Su, Li-Feng; Miao, Ji-Bin; Qian, Jia-Sheng; Chen, Peng (Journal of Research Updates in Polymer Science, 2013)
Maleic anhydride grafted POM (MAH-g-POM) was prepared and used as the compatibilizer for nitrile butadiene rubber (NBR) modified by acetal copolymer (POM) in different proportions. It was found that MAH-g-POM had good compatibilization effect for the blends. Both DSC and XRD results indicated that the process of blending POM with NBR considerably influenced the crystallization of POM. The scanning electron microscopy (SEM) study of tensile fracture surfaces of the blends clearly showed that the compatibility of NBR/POM blends was enhanced with increasing POM content. Mechanical properties indicated that NBR/MAH-g-POM had relatively higher elongation at break but lower tensile strength than NBR/POM blend. The present work will supply a good insight into the formula design and further optimization of polymer composites or blends.